'If the cap fits'? Probation staff and the changing nature of supervision in a Community Rehabilitation Company. (June 2020) - Tidmarsh, Matt
This article explores the changing nature of supervision in a Community Rehabilitation Company (CRC) following the Transforming Rehabilitation ( TR ) reforms to probation services in England and Wales. Based on an ethnographic study of an office within a privately owned CRC, it argues that TR has entrenched long-term trends towards 'Taylorised' probation practice. This is to say that qualitative and quantitative changes to the complexion of practitioners' caseloads since TR reflect a decades-long devaluation of the probation service and its staff. The decision to allocate most qualified practitioners to the National Probation Service means that Case Managers (i.e. probation service officers) now supervise offenders who would historically have been supervised by Senior Case Managers (i.e. probation officers). This loss of expertise has been exacerbated by administrative staff redundancies at the office. The result is an increasingly standardised and fragmented mode of working within the CRC in which the majority of services are now delivered by the voluntary sector.